Investigation of the role of reductant on the size control of Fe3O4 nanoparticles on rice straw - Khandanlou, Roshanak; Ahmad, Mansor; Shameli, Kamyar; Kalantari, Katayoon (North Carolina State University, 2014)
The goal of this study was to prepare nanocomposites of rice straw coated with different percentages of Fe3O4 nanoparticles (Fe3O4-NPs) [1.0, 5.0, 10.0, and 20.0 wt. %]. In this process, the size of Fe3O4-NPs changed with varying volumes of NaOH (2M). The Fe3O4-NPs were precipitated with sodium hydroxide from a solution of Fe(II) and (III) chloride in water under ambient conditions and N2 gas by the quick precipitation method using urea as a stabilizer. The rice straw/Fe3O4 nanocomposites (NCs) prepared by this method had magnetic properties in percentages higher than ten (10 wt. %). When the volume of NaOH increased, Fe3O4-NPs with uniform size and better distribution could be prepared, which means that the size of the NPs decreased as the reducing agent was increased. Transmission electron microscopy (TEM) showed that Fe3O4-NPs in rice straw were spherical with diameters from 18.47 to 9.93 nm. The SEM results show that the structure of rice straw underwent no particular change. EDX indicated the presence of Fe3O4-NPs on the surface of rice straw. X-ray powder diffraction (PXRD) indicated that the magnetic Fe3O4-NPs were pure and that the particles were small. The FT-IR results showed that the Fe3O4-NPs were successfully coated on the surface of rice straw.